A USAGE OF RESOURCE EDITOR IN VISUAL BASIC - LAVRINCIK, Jan (Trends in education, 2011)
The article deals with significance creation and use control element Resource Editor of Visual Basic in education. The choice of programming language is emphasized from the field of expert demands and expansion of abstract thinking in student PdF UP. At the end, it discusses about the new units programming language Microsoft Visual Basic 6 of practical of programming in PdF UP.
Keywords: Resource Editor; Visual Basic; instruction LoadRes; String Table; RES files.